PRINCIPALS’ LEADERSHIP STYLES AND STUDENTS’ DISCIPLINE IN PUBLIC SECONDARY SCHOOLS IN RIVERS STATE - Amaefule Marcella M. C.; Amaechi Anderson Iheanyi (African Journal of Educational Management, 2021)
This study investigated the influence of principals’ leadership styles on students’ discipline in public secondary schools in Rivers State. Descriptive survey design was adopted for the study. Four research questions and four hypotheses guided the study. The study used a selfdeveloped questionnaire titled ‘Principals Leadership Style on Students Discipline (PLSD)’ as the instrument for data collection. The total population of the study was 41,790 made up of teachers, principals and SSII students. A stratified random sampling technique with the help of Taro Yamen was employed to select the sample size of 492 students, 153 teachers and 18 principals. Test-retest method was adopted to test the reliability of the instrument and Pearson Product Moment Correlation was used to analyze the data and a reliability coefficient of 0.84 and 0.81were obtained for the students and school authorities instruments respectively. Simple linear regression was used to answer the research questions. The result revealed an R2 of 0.57, 0.45, 0.53, and 0.79 for autocratic, democratic, transactional and translational leadership styles respectively. This showed that principal’s autocratic leadership style to a very moderate extent influences student discipline in public secondary schools in Rivers State. It also revealed that principal’s democratic leadership style has low influence on students discipline in public secondary schools in Rivers State. Furthermore, the result also revealed that principal transactional leadership style to a very moderate extent influences students discipline in public secondary schools in Rivers State while Principals transformational leadership style to a very high extent influences students discipline in public secondary schools in Rivers State. Therefore, it was recommended among others that training and development programmes should be given to principals and vice principals to update them with current global leadership style that achieve results.